2017
DOI: 10.1080/21622965.2017.1407653
|View full text |Cite
|
Sign up to set email alerts
|

Differential long-term medication impact on executive function and delay aversion in ADHD

Abstract: The objective was to compare long-term effects of methylphenidate (MPH) and atomoxetine (ATX) on executive functions (EF) and delay aversion (DAv) in ADHD. A randomized controlled trial was conducted. A comprehensive neuropsychological battery was administered at three moments (Naive, Post-1, Post-2). ADHD participants who showed deficits in the naive evaluation (n = 26) were randomized to receive either MPH (n = 13; M = 11 ± 1, M 96 ± 8) or ATX (n = 13; M = 10 ± 1, M 106 ± 16.5) optimal dosages. Parallel test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…Our finding that OROS-MPH results in improvements on a CI task were consistent with some (Shiels et al, 2009) but not all studies examining CI in youth with ADHD (Devito et al, 2008; Rubio-Morell & Hernández-Expósito, 2019). Notably, previous studies failing to find a significant effect of stimulant medication on CI have utilized tasks with hypothetical delays and rewards whereas the current study and others finding an effect of stimulant medication on CI incorporate experiential delays (Shiels et al, 2009) or measured CI through questionnaires (Low et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that OROS-MPH results in improvements on a CI task were consistent with some (Shiels et al, 2009) but not all studies examining CI in youth with ADHD (Devito et al, 2008; Rubio-Morell & Hernández-Expósito, 2019). Notably, previous studies failing to find a significant effect of stimulant medication on CI have utilized tasks with hypothetical delays and rewards whereas the current study and others finding an effect of stimulant medication on CI incorporate experiential delays (Shiels et al, 2009) or measured CI through questionnaires (Low et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The effect of stimulant medication, the most common treatment for children with ADHD (Polanczyk et al, 2007), on task-based and questionnaire-based measures of decision-making has been systematically evaluated in only a handful of studies utilizing methylphenidate (DeVito et al, 2008; Low et al, 2018; Rubio-Morell & Hernández-Expósito, 2019; Shiels et al, 2009). Collectively, methylphenidate appears to result in reduced CI in some (Low et al, 2018; Shiels et al, 2009), but not all studies (Devito et al, 2008; Rubio-Morell & Hernández-Expósito, 2019). Part of this discrepancy may reflect the fact that these studies have utilized a number of different measures to assess CI.…”
mentioning
confidence: 99%
“…Therefore, atomoxetine has a better effect on the long-term treatment of ADHD and patients with psychiatric symptoms (35,69). In addition to improving the core symptoms of ADHD, atomoxetine can also improve multiple functions of children with long-term treatment, including learning function, peer relationship, family relationship, cognitive function, executive function, social function and so on (8,(140)(141)(142)(143). Some studies have shown that common comorbidities (such as ODD, anxiety disorder, TD and ASD) in ADHD patients are unaffected or improved after atomoxetine therapy (16,27,35,72,73).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that stimulants improve executive functioning (Rubio Morell and Hernandez Exposito, 2017) resulting in better prefrontal control leading to less impulsive choices (Arnsten, 2009). Moreover, stimulants given to ADHD individuals have been shown to improve ability to delay reward (Shiels et al, 2009).…”
Section: Introductionmentioning
confidence: 99%